A scoping review of shoulder kinesthetic function in individuals with diabetes mellitus, with and without frozen shoulder - Neena Varghese; Mamta S. Shetty; Rajani Prashant Mullerpatan (MGM Journal of Medical Sciences)
Background: Kinesthesia, the ability to perceive movements, is diminished in individuals with type II diabetes mellitus. People with frozen shoulders also experience kinesthetic deficits. Thus, obtaining accurate information on shoulder kinesthetic function in individuals with diabetes mellitus, both with and without a frozen shoulder, will aid in developing preventive and therapeutic strategies to optimize shoulder function. Aim: The study aims to investigate kinesthetic deficits in the shoulder among individuals with diabetes mellitus, both with and without frozen shoulder. Materials and Methods: A thorough literature search was performed using PubMed, Cochrane, CINAHL, and Science Direct. Free full-text articles in English, published from 2010 to October 2020, were identified using keywords and MeSH terms. Inclusion and exclusion criteria were developed based on the PICO format. The search results were then screened to identify relevant articles for this scoping review. Results: This review included fourteen articles, encompassing systematic reviews, cross-sectional studies, and prospective studies. Six studies examined the impact of diabetes mellitus on shoulder kinesthesia. These kinesthetic deficits adversely affected basic daily activities, recreational pursuits, and occupational tasks. Conclusion: Reduced kinesthetic function in the shoulder is attributed to structural changes such as capsular tightness, alterations in the fascicle length of rotator cuff muscles, the long head of the biceps, and glenohumeral joint laxity. Factors contributing to the loss of kinesthetic function include muscular fatigue from repetitive shoulder motion, limited joint mobility, blood glucose levels, and decreased muscle strength. This study provides valuable insights for clinicians to design rehabilitation programs, enhance shoulder function, and prevent re-injury risk.